How to measure a quale - Pessoa Jr., Osvaldo Frota (Sofia, 2019)
According to the colored-brain thesis (or qualitative physicalism), sense data or qualia are real physical-chemical qualities, located inside the brain, possibly at a specific locus. Our hypothesis is that the seats of phenomenal consciousness have a structure and a materiality. According to the proposed view, a chromatic quale emerges when a certain pixel of the visual sensorium (the hypothetical subjective visual “screen”, or Cartesian theater, with its specific materiality ω) is fed with a certain pattern Σ of spikes; a change in this pattern quickly changes the color that is subjectively generated. How could one manage to measure chromatic qualia? In principle, with nanoscopical techniques, one could capture all the patterns that fall on the sensorium, and transmit the information to other media. But this does not capture the qualia. However, if the patterns are made to fall on a tissue of the same kind, typically inside another person’s brain, this other person will have roughly the same subjective experience as the first person. The model is used to explore two different situations involving qualia inversion. The paper also explores Cartesian materialism, and the claim that phenomenal time and space are identical to a region of physical time and space.